Passive cooling of highly-concentrator triple-junction solar cell using a straight-finned heat sink: An experimental investigation. (December 2022) - Refaey, H.A.; Abdelrahman, M.A.; Alharthi, Mathkar A.; Bendoukha, Samir; Khan, Said Ghani; Emam, Mohamed
Abstract: Herein, an experimental setup in Saudi Arabia's hot weather conditions is used to assess the electrical and thermal performance of concentrator photovoltaic triple junction (CPV TJ) cells fed through various Fresnel lenses with concentration ratios (CRs) ranging from 30.5 to 109 suns. The thermal characteristics of triple junction solar cells are investigated in passive cooling utilizing two straight-finned heat sinks with dimensions 40 × 40 mm (HS-A) and 40 × 100 mm (HS–B). Results show that the temperature and power production of the cells increases with the solar concentration ratio, whereas its efficiency decreases. It is found that using a heat sink, reduces the cell's temperature and improves heat uniformity. The larger heat sink (HS–B) performs better since it maintains the cell operating temperature at 44.7, 46.8, and 52.5 °C for the CRs of 68, 80, and 109 suns, respectively, compared to 46.5, 55.4, and 66.4 °C for the smaller one (HS-A) under the same operating conditions. Furthermore, at a CR of 68 suns, the TJ cell with the aluminium finned heat sink generates an electric output of 2.32 W/cm 2 using HS-B and 2.29 W/cm 2 using (HS-A), compared to 2.22 W/cm 2 produced by the uncooled cell without heat sink under the same conditions.